2016
DOI: 10.1186/s12888-016-1114-0
|View full text |Cite
|
Sign up to set email alerts
|

Pre-discharge factors predicting readmissions of psychiatric patients: a systematic review of the literature

Abstract: BackgroundReadmission rate is considered an indicator of the mental health care quality. Previous studies have examined a number of factors that are likely to influence readmission. The main objective of this systematic review is to identify the studied pre-discharge variables and describe their relevance to readmission among psychiatric patients.MethodsStudies on the association between pre-discharge variables and readmission after discharge with a main psychiatric diagnosis were searched in the bibliographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
121
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(140 citation statements)
references
References 64 publications
16
121
2
1
Order By: Relevance
“…They were particularly likely among patients who had required a transitionary period in a local hospital before discharge to the community. Donisi, Tedeschi, Wahlbeck, Haaramo, and Amaddeo (2016), reviewing predischarge factors and readmission, found that the most consistent significant predictor of readmission was prior hospitalisation-which was consistent with our findings. In addition, our readmission rate of offender patients with substance misuse disorders was high, also fitting with the result of previous reports (Donisi et al, 2016;Mark et al, 2013).…”
Section: Readmission and Risk Factorssupporting
confidence: 91%
See 1 more Smart Citation
“…They were particularly likely among patients who had required a transitionary period in a local hospital before discharge to the community. Donisi, Tedeschi, Wahlbeck, Haaramo, and Amaddeo (2016), reviewing predischarge factors and readmission, found that the most consistent significant predictor of readmission was prior hospitalisation-which was consistent with our findings. In addition, our readmission rate of offender patients with substance misuse disorders was high, also fitting with the result of previous reports (Donisi et al, 2016;Mark et al, 2013).…”
Section: Readmission and Risk Factorssupporting
confidence: 91%
“…Donisi, Tedeschi, Wahlbeck, Haaramo, and Amaddeo (2016), reviewing predischarge factors and readmission, found that the most consistent significant predictor of readmission was prior hospitalisation-which was consistent with our findings. In addition, our readmission rate of offender patients with substance misuse disorders was high, also fitting with the result of previous reports (Donisi et al, 2016;Mark et al, 2013). Although we do not have all details for the local hospital readmissions, it is perhaps worth emphasising that a hospital admission is not necessarily an indication of failure.…”
Section: Readmission and Risk Factorssupporting
confidence: 91%
“…With regard to the marital status, a recent review pointed out that being married generally appears to be a protective factor against readmission of patients suffering from psychiatric diseases (11). According to the literature, this observation also applies to readmission in SUD (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding factors that predict readmission would allow to better address the specific needs of the population at risk and to prevent costly inpatient treatment. In addition, readmission rates might serve as an indicator of the quality of care and could therefore be of particular relevance for healthcare policy makers (11). Finally, previous readmission rates in SUD are often considered to be a significant predictor of further relapse after inpatient treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation